2021
DOI: 10.3390/ph14070659
|View full text |Cite
|
Sign up to set email alerts
|

Merging the Multi-Target Effects of Kleeb Bua Daeng, a Thai Traditional Herbal Formula in Unpredictable Chronic Mild Stress-Induced Depression

Abstract: Major depressive disorder (MDD) is a common and debilitating psychiatric disease characterized by persistent low mood, lack of energy, hypoactivity, anhedonia, decreased libido, and impaired cognitive and social functions. However, the multifactorial etiology of MDD remains largely unknown due the complex interaction between genetics and environment involved. Kleeb Bua Daeng (KBD) is a Thai traditional herbal formula that has been used to promote brain health. It consists of a 1:1:1 ratio of the aerial part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Mice with despair behavior mainly manifest immobility. Here, the FST and TST were performed to test the despair behavior of mice via measuring latency to immobility and immobility time (Guo et al, 2021; Maneenet et al, 2021). The results showed that mice susceptible to depression manifested significant despair, consistent with the results regarding sucrose preference.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with despair behavior mainly manifest immobility. Here, the FST and TST were performed to test the despair behavior of mice via measuring latency to immobility and immobility time (Guo et al, 2021; Maneenet et al, 2021). The results showed that mice susceptible to depression manifested significant despair, consistent with the results regarding sucrose preference.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study suggested that KBD ameliorated cognitive impairment in unpredictable, chronic, mild, stress-induced rat via the improvement of antioxidant capacity of the flavonoid, phenolic acid, and triterpene glycosides, which are constituents of the plant ingredients [30]. We recently analyzed the phytochemicals in the KBD formulation and found that the herbal medicine was rich in asiaticoside and madecassoside (major active constituents of CA), piperine (a major component of PN), kaempferol, quercetin, rutin, kaemferol-3-glucoside, luteolin-7-O-glucoside, and ferulic acid (major constituents of NN) [30,55]. The major phytochemicals found in the KBD formula were triterpene glycosides-madecassoside (179 mg/g ex-tract) and asiaticoside (57 mg/g extract)-and alkaloid piperine (10 mg/g extract).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it significantly attenuated hypothalamic-pituitary-adrenal axis dysregulation by upregulating glucocorticoid receptor expression but downregulating serum- and glucocorticoid-inducible kinase 1 and FK506 binding protein 5 expression in unpredictable chronic mild stress (UCMS)-induced mice. Furthermore, black-pepper fruit extract with Kleeb Bua Daeng normalized proinflammatory cytokine expression, including TNF-α, IL-1β, and IL-6, and had an inhibitory effect on MAO A and B in vitro [ 120 ]. Similarly, Maneenet et al showed that oral administration of black-pepper fruit extract with Kleeb Bua Daeng to UCMS-induced mice significantly improved their cognitive function.…”
Section: Neuroprotective Effects Of Black Pepper and Piperine In Age-...mentioning
confidence: 99%